Effects of Enhanced A/O-MBR on Treating Domestic Sewage with Low C/N Ratio and Membrane Fouling - YANG Chao; LI Jie; MA Donghua (Renmin Zhujiang)
By adding polyurethane foam (PUF) carriers in a conventional A/O-MBR (CMBR),an enhanced A/O-MBR (HMBR) is developed and operates in parallel with CMBR to treat domestic sewage with a low C/N ratio.The results reveal that the effluent quality by HMBR is significantly better than that by CMBR.The average removal rates of COD,ammonia nitrogen,and total nitrogen by HMBR are 83.88%,67.24%,and 50.39%,respectively,while those by CMBR are 81.96%,59.97%,and 46.32%,respectively.In addition,HMBR and CMBR reach the lowest membrane flux,i.e.,0.19 and 0.20 L/(m2·h),on the 46th and 70th days of continuous operation,respectively.HMBR can effectively prolong the operation time of the membrane module and reduce the degree of fouling,and it can recover to 46.50% of the initial membrane flux after physical flushing and 93.7% of the initial membrane flux after physical-chemical washing.Therefore,the addition of PUF carriers not only strengthens the treatment performance of A/O-MBR but also effectively reduces membrane fouling.